Evaluation of genetic variability in fragrant rose (Rosa × hybrida L.) cultivars under open field cultivations (Current Horticulture, 2024)
Twenty six rose (Rosa × hybrida L.) cultivars grown for open field conditions were characterized using 16 vegetative and floral  traits to obtain information on the nature and magnitude of existing genetic variability. The cultivars, Night Time, Christian Dior  and Pusa Abhishek were early in flowering and Local Collection 3, Local Collection 4, Kashmir Velvet and Edouard had longer  flowering duration; Christian Dior and Bonne Nuit had bigger flowers; Pusa Bahadur had long flower stalk; Local Collection  3, Local Collection 4, Edouard and Kashmir Velvet were having more number of flowers per plant and Pusa Bahadur, Night  Time and Christian Dior were found with higher flower weight and shall help in further selection and hybridisation. The higher  genotypic and phenotypic coefficients of variation were recorded for plant height, plant spread (E-W), plant spread (N-S),  stem girth, number of shoots/ plant, number of petals/ flower, flower stalk length, number of flowers/ plant and 100-flower  weight, indicating that genotypic variation contributed markedly towards total variability for the above traits. There is a greater  scope for selection in improving flower yield. The high heritability with high expected genetic advance over mean (GAM)  was observed for plant height, plant spread (E-W), plant spread (N-S), stem girth, number of shoots/ plant, flower bud length,  flower diameter and flower stalk length. This also revealed the lesser influence of environment on these traits. Therefore, simple  selection based on phenotypic values for these traits could be useful in their improvement for achieving higher flower yield. The  trait specification identified genotypes could ideally be used as donor parents in rose breeding programme to develop desired  genotypes for open field cultivation.
Keywords: Genetic characterization; Heritability; Morphological traits